2011
DOI: 10.3747/co.v18i2.701
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Economic Analysis of U.S. Oncology Adjuvant Trial 9735

Abstract: alternative to ac in Canadian clinical practice for the adjuvant treatment of operable early breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The findings of the study in America that examined the cost of metastatic breast cancer showed that the cost of treatment was 44%, the cost of palliative and supportive was 31% and lost productivity was 21% of the total cost of metastatic breast cancer (Sorensen et al, 2012). In the study of Bernard, 70% of the total costs in AC arm was related to the cost of chemotherapy (Bernard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the study in America that examined the cost of metastatic breast cancer showed that the cost of treatment was 44%, the cost of palliative and supportive was 31% and lost productivity was 21% of the total cost of metastatic breast cancer (Sorensen et al, 2012). In the study of Bernard, 70% of the total costs in AC arm was related to the cost of chemotherapy (Bernard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the high cost of the PG regimen was due to the costs of chemotherapy drugs in PG regimen and the Gemcitabin on the eighth day (Chen et al, 2002). Bernard et al in 2011, Younis et al in 2011 and Liubao in separate studies showed that the low cost of the AC regimen was due to the costs of chemotherapy drugs in AC regimen (Liubao et al, 2009;Bernard et al, 2011;Younis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] In previous studies, the low cost of AC regimen was due to costs of chemotherapy drugs. [ 25 27 28 ] The results of this study showed that the response to treatment in AC chemotherapy regimen with 84% was higher than PG chemotherapy regimen with 75%. In a study which conducted by Colomer et al .…”
Section: Discussionmentioning
confidence: 78%
“…showed that 70% of the total costs in AC was associated with the cost of chemotherapy. [ 25 ] Furthermore, in the Chen et al ., study 65% of total costs in PG was related to the cost of chemotherapy. [ 26 ] Chen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation